2008
DOI: 10.1186/1751-0147-50-25
|View full text |Cite
|
Sign up to set email alerts
|

Post mortem findings in sows and gilts euthanised or found dead in a large Swedish herd

Abstract: Background: The aim of this study was to get information on post mortem diagnoses of sows found dead or euthanised and to understand the diagnoses aetiology (causative background). Moreover, the study was to evaluate the association between the clinical symptoms observed on farm and post mortem findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
1
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 12 publications
8
37
1
12
Order By: Relevance
“…No factors appeared to be statistically significant in the logistic regression analysis in which the outcome variables were 'sudden death' and 'euthanasia'. That 'lameness' was not significantly associated with euthanasia disagrees with other studies, which have found lameness to be the most commonly observed reason for euthanasia among sows and gilts (Kirk et al, 2005;Engblom et al, 2008). As herds in this study were visited twice by technicians who performed clinical registrations on individual sows, they could have made farmers more aware of clinical signs of lameness.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…No factors appeared to be statistically significant in the logistic regression analysis in which the outcome variables were 'sudden death' and 'euthanasia'. That 'lameness' was not significantly associated with euthanasia disagrees with other studies, which have found lameness to be the most commonly observed reason for euthanasia among sows and gilts (Kirk et al, 2005;Engblom et al, 2008). As herds in this study were visited twice by technicians who performed clinical registrations on individual sows, they could have made farmers more aware of clinical signs of lameness.…”
Section: Discussioncontrasting
confidence: 86%
“…Among 14 526 culled sows in 37 Danish sow herds with group-housed pregnant sows, 10% of the sows were euthanized and 11% died suddenly (Vestergaard et al, 2006). Problems in relation to the locomotion system (such as arthritis and osteochondosis) are reported to be the most common reason for euthanizing sows in systems with group-housed pregnant sows (Kirk et al, 2005;Engblom et al, 2008). Kirk et al (2005) found locomotive disorders to be the primary cause of euthanization in more than 70% of 172 euthanized sows examined post mortem.…”
Section: Introductionmentioning
confidence: 99%
“…El tamaño y la cantidad de quistes presentes en cada ovario son variables, pudiendo ser grandes o pequeños, múltiples o simples y uni o bilaterales. En estudios realizados mediante ultrasonografía de tipo B (USG-B), la prevalencia de QOv varió entre el 2 % y el 30 % en el animal vivo (Cianciolo & Mohr, 2007), mientras que en estudios realizados en planta de faena fue de 7 % a 13 % (Barrales et al, 2014;D´Allaire et al, 2006;Engblom et al, 2008;Heinonen et al, 1998;Knauer et al, 2007;Rodríguez et al, 2008;Tummaruk et al, 2009).…”
Section: Quistes Ováricosunclassified
“…Esto se debe al impacto económico y productivo que representan la compra y preparación de nuevas reproductoras (D´Allaire et al, 1987(D´Allaire et al, , 1992Engblom et al, 2008;Knauer et al, 2007;Sasaki et al, 2010;Vargas et al, 2009).…”
Section: Introductionunclassified
“…In some cases, euthanasia may be the best option for the well-being of the pig 11) . In Sweden, euthanasia has been well practiced because of the animal welfare legislation, which states that only females in normal body condition and without lameness are allowed to be transported to slaughter 6) . In fact, the proportion of euthanized sows on commercial farms was 10.5 , which was higher than the 4.3 of dead sows 5) .…”
mentioning
confidence: 99%